Novel taxa of Diatrypaceae from Para rubber (Hevea brasiliensis) in northern Thailand; Introducing a novel genus Allocryptovalsa - C. Senwanna (2018)
© Guizhou Academy of Agricultural Sciences. Species of Diatrypaceae are widespread on dead wood of plants worldwide. The delineation of this family is rather problematic because the characters of ascostromata are extremely variable and the names of taxa with sequence data are often misleading. In this paper, species of Diatrypaceae were collected from Para rubber in northern Thailand for examination and illustrations. Based on morphological characteristics and phylogenetic analyses, a new genus, Allocryptovalsa, is introduced to accommodate a new species A. polyspora and two species, A. cryptovalsoidea and A. rabenhorstii rabenhorstii rabenhorstii are transferred to the new genus. The new species, Diatrypella heveae and Peroneutypa longiasca are also introduced in this paper. Phylogenetic analyses of combined ITS and ß-tubulin sequence data show their phylogenetic affinities in Diatrypaceae. Our study also shows that phylogenetic analyses of taxa of Diatrypaceae are highly confused as some genera are shown to be polyphyletic.